2020
DOI: 10.17478/jegys.804939
|View full text |Cite
|
Sign up to set email alerts
|

The acceptance of school counselor in the use of ICT during school from home in the Covid-19 era

Abstract: The Covid-19 pandemic marks an era of using online as a medium of learning communication, including counseling services. School Counselor are required to use ICT as a form of adaptation to learning with students. The research design using a quantitative Structural equation modeling aimed to test correlation of two or more variables. The participants are 214 School Counselor who are members of the Indonesian Guidance and Counseling Association (ABKIN) and the Guidance and Counseling Teacher Council (MGBK). This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The role of technology in education has been gaining importance over the years and its use in classrooms is becoming increasingly relevant [8]. Due to the COVID-19 pandemic, the education system as well as many other areas are being disrupted.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of technology in education has been gaining importance over the years and its use in classrooms is becoming increasingly relevant [8]. Due to the COVID-19 pandemic, the education system as well as many other areas are being disrupted.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The educational counsellor needs to innovate to adequately apply ICT in the counselling process [8], but it seems that, faced with this difficult situation, counsellors do not adequately optimise technology in the counselling process [22]. One of these reasons may be a lack of knowledge and confidence in ICT on the part of counsellors; the correct performance of these tasks depends above all on both initial and continuous training of guidance practitioners [9].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital information technology helps in improving the relations with students who have grown up in a digital environment. Further, it helps students who tend to use electronic communications as a method of learning using digital multimedia means (Abdillah et al, 2020 ). The results of the study conducted by Dores et al, ( 2020 ) revealed that the use of digital information technology is a positive experience as it meets the commitment of counselees and achieves positive results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital information technology also reduces costs, provides direct access to individuals, and increases the processes of collaboration, communication, and coordination. The use of digital information also helps in improving communication and working relations with students who have grown up in a digital environment, and it helps students who wish to use electronic communication as a methodology of learning using digital equipment (Abdillah et al, 2020 ). The results of Emmanuel’s ( 2020 ) study indicated that teachers’ perceptions of e-counseling created a positive self-image and contributed to improving their academic performance, time management skills, and providing appropriate services for students.…”
Section: Literature Reviewmentioning
confidence: 99%